2009
DOI: 10.1080/00365520903171276
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic mechanisms of postinfectious functional gastrointestinal disorders: Results 3 years after gastroenteritis

Abstract: Three years after salmonellosis, PI-FGID patients showed no evidence of inflammation in the gastric or colonic mucosa, but visceral sensitivity and anxiety/somatization levels were increased. The close anatomical mast cell-nerve fibers relation does not seem to be related to the FGID but to the infection itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 45 publications
6
25
1
5
Order By: Relevance
“…This hypothesis is supported by studies that have demonstrated a higher prevalence of symptoms compatible with IBS in individuals with a prior history of acute enteric infection, compared with those without such exposure [42, 60, 61]. The fact that population-based studies demonstrate a link between mucosal eosinophilia in FGID patients and co-existing colonic spirochetosis [44] is also consistent with the concept of an infectious agent [62, 63]. Besides the histological evidence of mucosal inflammation, some investigators have shown activation of the immune system in patients with IBS, reflected by increased levels of cytokines in the colonic mucosa [64], as well as an increase in release of proinflammatory cytokines from isolated PBMCs, particularly in patients with IBS-D [16], and also in patients with FD [65].…”
Section: Evidence For Low-grade Mucosal Inflammation Immune Activatisupporting
confidence: 71%
“…This hypothesis is supported by studies that have demonstrated a higher prevalence of symptoms compatible with IBS in individuals with a prior history of acute enteric infection, compared with those without such exposure [42, 60, 61]. The fact that population-based studies demonstrate a link between mucosal eosinophilia in FGID patients and co-existing colonic spirochetosis [44] is also consistent with the concept of an infectious agent [62, 63]. Besides the histological evidence of mucosal inflammation, some investigators have shown activation of the immune system in patients with IBS, reflected by increased levels of cytokines in the colonic mucosa [64], as well as an increase in release of proinflammatory cytokines from isolated PBMCs, particularly in patients with IBS-D [16], and also in patients with FD [65].…”
Section: Evidence For Low-grade Mucosal Inflammation Immune Activatisupporting
confidence: 71%
“…This concept was first proposed almost 20 years ago [15], and in latter years has been supported by numerous studies that demonstrate a higher prevalence of symptoms compatible with IBS in individuals with prior exposure to acute enteric infection, compared with those without such exposure [16][17][18][19][20]. A few studies have demonstrated increased levels of pro-inflammatory cytokines and higher numbers of mast cells [20][21][22], the latter in close proximity to enteric nerve fibers in the GI mucosa of these individuals.…”
Section: Introductionmentioning
confidence: 89%
“…Esta circunstancia se ha observado en un estudio prospectivo realizado por este grupo, en el que a los 3 años de un brote de gastroenteritis aguda por Salmonella la mucosa de pacientes en los que se había desarrollado SII o DF mostraba un número similar de células inmunes y una producción de citocinas equiparable a los controles 47 (fig. 4).…”
Section: Síndrome Del Intestino Irritable Postinfeccioso: Un Posible unclassified